A Novel Patient Safety Event Reporting Tool in Otolaryngology. (July 2017) - Vila, Peter M.; Lewis, Sean; Cunningham, Gene; Brereton, Jean; Espinel, Alexandra G.; Roberson, David W.; Shah, Rahul K.
Objective: To report the results of a preliminary analysis of a quality improvement initiative aimed to identify potential latent systems defects. Methods: A pilot study of an anonymous, voluntary, event reporting system made available to all members of the American Academy of Otolaryngology—Head and Neck Surgery was performed. The National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP) index was used to classify error types. Descriptive statistics were used to summarize submissions to the database. Results: In the 53 cases reported to the database over 22 months, the majority involved errors that had resulted in harm (n = 34, 64%), followed by errors that occurred and did not result in harm (n = 7, 13%). Errors occurred predominantly in the hospital (n = 23, 44%) and operating room (n = 19, 35%). Most entries were classified as either technical (n = 21, 39%) or related to postoperative care (n = 15, 30%). Discussion: This preliminary descriptive analysis of a novel otolaryngology patient safety event reporting tool shows that this platform brings unique value to the identification of errors and adverse events in our specialty. Most reported events were classified as errors resulting in harm. The most common type of reported event was a technical error, most often resulting in a nerve injury. Implications for Practice: This reporting tool will likely allow for identification and prioritization of improvement opportunities. This example may serve as a guide for other societies to create similar platforms as we strive for a standardized process for event reporting.